Integration von Palliativmedizin in onkologische Spitzenzentren Deutschlands - ambulante Sprechstunden und Rotationsprogramme der spezialisierten Palliativmedizin - Berendt, Julia; Thomas, Michael; Neukirchen, Martin; Schwartz, Jacqueline; Hense, Jörg; Tewes, Mitra (TumorDiagnostik & Therapie, 2019)
Background Comprehensive Cancer Centers are characterized by interdisciplinary exchange for meeting increasingly complex care needs during the course of the disease. Tumor consultations hours and fellowship rotations build hereby bridges between the subjects and disciplines. Objectives In order to be able to provide support in the Comprehensive Cancer Center Network for the further integration of specialized palliative medicine, it was highlighted to what extent consultation hours and fellowship rotations for the palliative care are integrated into the centers. Methods Information about the spS and fellowship rotation of the Comprehensive Cancer Center (n=16), which had previously been funded by the Cancer Aid, was paper-based collected with a survey questionnaire. For this purpose, the heads of the palliative care departments of the centers were interviewed from July to August 2017. The evaluation was performed by SPSS (frequency, mean value, median, range). Results 15 from 16 centers responded to the survey (93.75%). Nine centers (60%) have a consultation hour for palliative care. Four from nine centers can submit this offer for ≥4 hours (44.4%). Fellowship rotations in the palliative care occur primarily in all centers from oncology/hematology (n=11, 73.3%) and anaesthesia (n=6) and often for a twelve months (n=11) period of time. Conclusion Outpatient structures of the palliative care have been insufficiently implemented to a consultation hour within Comprehensive Cancer Centers. The existing effort to integrate palliative care into the oncological course of disease requires further structuring in order to increase the visibility of palliative care services. Fellowship rotations in the palliative care department are regularly implemented in the network even if only for some of the subjects in order to raise awareness of the possibilities of the palliative care.
CRIS-Team Scopus Importer:2019-06-21
Keywords: consultation; fellowships; outpatient clinics; palliative care